Enhanced protective antibody to a mutant meningococcal factor H-binding protein with low-factor H binding - Granoff, Dan M. (JCI Insight, 2016)
Meningococcal factor H-binding protein (FHbp) is an antigen in 2 serogroup B meningococcal vaccines. FHbp specifically binds human and some nonhuman primate complement FH. To investigate the effect of binding of FH to FHbp on protective antibody responses, we immunized infant rhesus macaques with either a control recombinant FHbp antigen that bound macaque FH or a mutant antigen with 2 amino acid substitutions and >250-fold lower affinity for FH. The mutant antigen elicited 3-fold higher serum IgG anti-FHbp titers and up to 15-fold higher serum bactericidal titers than the control FHbp vaccine. When comparing sera with similar IgG anti-FHbp titers, the antibodies elicited by the mutant antigen gave greater deposition of complement component C4b on live meningococci (classical complement pathway) and inhibited binding of FH, while the anti-FHbp antibodies elicited by the control vaccine enhanced FH binding. Thus, the mutant FHbp vaccine elicited an anti-FHbp antibody repertoire directed at FHbp epitopes within the FH binding site, which resulted in greater protective activity than the antibodies elicited by the control vaccine, which targeted FHbp epitopes outside of the FH combining site. Binding of a host protein to a vaccine antigen impairs protective antibody responses, which can be overcome with low-binding mutant antigens.